Depression and sleep quality in older adults - Ghaida, Nafisa Siti; Fitriana, Lisna Anisa; Suparto, Tirta Adikusuma (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Aging causes physiological and psychological changes that increase elderly vulnerability to depression and sleep disturbances, negatively impacting quality of life. Purpose: To analyze the relationship between depression and sleep quality among the elderly at Garut residential care facility for the elderly. Method: A quantitative cross-sectional study was conducted using purposive sampling (n=53). Instruments included the Geriatric Depression Scale (GDS) and the Pittsburgh Sleep Quality Index (PSQI). Data were analyzed using univariate and bivariate methods. Results: Univariate analysis showed that 79.2% of respondents had poor sleep quality, and 47.2% experienced depression (35.8% mild, 5.7% moderate, 5.7% severe). Bivariate analysis revealed a statistically significant, positive, but weak correlation between depression and sleep quality (r=0.303; p=0.028). Conclusion: This study reveals a weak yet significant link between depression and sleep quality among elderly residents, with other emotional, social, physical, and environmental factors also contributing. The findings highlight the need to address both mental health and environmental conditions to improve overall quality of life.